Evaluation of Thermographic Imaging in Canine Hindlimb Muscles After 6 Min of Walking—A Pilot Study - Repac, Jennifer; Alvarez, Leilani X.; Lamb, Ken; Gillette, Robert L. (Frontiers in Veterinary Science, 2020)
Objective: To evaluate changes in superficial temperature of hindlimb muscles before and after a 6-min walk in healthy dogs. Methods: Two infrared thermographic images were captured of the proximal and distal hindlimbs of 11 healthy dogs before and after a 6-min walk. Orthopedic exam and objective gait analysis confirmed the healthy status of study subjects. Superficial temperatures of the gastrocnemius, biceps femoris, and gracilis were assessed. Analysis of images was performed using 2 different methods of region of interest (ROI) selection. ROI were selected first using one point (single pixel) in the muscle and then separately by selecting a line (LN) corresponding to many points of each muscle belly from which an average was taken. P < 0.05 was considered significant. Results: There was no significant change in temperature using point ROI before and after 6 min of walking of the gastrocnemius, gracilis, and biceps femoris muscles (p = 0.273, p = 0.349, p = 0.351, respectively). Using linear ROI, both biceps femoris and gracilis muscles exhibited significant increases in temperature (p < 0.0001, p = 0.032, respectively). There was no significant increase in temperature of gastrocnemius muscle for both point and linear ROI selection (p = 0.273, p = 0.448, respectively). The right biceps femoris temperatures were higher compared to left biceps femoris using the linear ROI before and after walks (p < 0.0001). The overall (left and right limbs pooled) standard deviation of point selected values were greater than LN selected values of the biceps femoris (1.35 and 1.11) and gastrocnemius (1.51 and 1.23). In contrast, standard deviation for the gracilis measurements were decreased using point selection vs. LN selection (1.09 and 1.3). Conclusions: The biceps femoris and gracilis muscles demonstrated significant increases in surface temperature after 6 min of walking using the linear method of ROI. Measurement of numerous points along the entire length of the biceps femoris and gastrocnemius muscles may provide a more accurate assessment of the increased vascularity within the tissues resulting from work compared to single point selection. Clinical Significance: Prior activity and ROI selection method should be considered when interpreting thermography results.